ASSOCIATION OF CIRCULATING HYPOXIA- INDUCIBLE FACTOR 1 ALPHA WITH TYPE 2 DIABETES IN INDIVIDUALS WITH SEVERE OBESITY - Pandian, Bhuvaneswari; Moh, Angela; Cheng, Anton; Sum, Chee Fang; Subramaniam, Tavintharan; Lim, Su Chi (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Obesity and type 2 diabetes (T2D) are often attributed to hypoxia. Adaptive responses to hypoxia are regulated by hypoxia-inducible factor 1 α (HIF1α). The role of hyperglycemia in mediating HIF1α expression and activity remains unclear. This cross-sectional study aimed to evaluate the relationship between plasma HIF1α and T2D in individuals with severe obesity. METHODOLOGY The study involved adults with severe obesity recruited at the Khoo Teck Puat Hospital (N=252, age: 45±8 years, 38% men, body mass index: 41.1 ± 6.5 kg/m2). The level of HIF1α in plasma was measured by immunoassay. Spearman’s correlation and modified Poisson regression analysis were used to evaluate the association of HIF1α with glycated haemoglobin (HbA1c) and T2D, respectively. RESULTS Out of 252 subjects, 52 %(n = 131) of the subjects had T2D. A positive correlation was observed between HIF-1α and HbA1c (rho = 0.295, P<0.001). Individuals with T2D had markedly higher median HIF1α levels compared with their non-T2D counterparts [207.1 (IQR:180.4−246.1) vs 155.1 (IQR:132.0−189.6) pg/ml; P<0.001)]. The association between natural log-transformed circulating HIF1α and T2D (outcome) remained significant even after adjusting for age, gender, body mass index and HbA1c (risk ratio: 2.63, 95% CI: 1.85−3.74, P<0.001). CONCLUSION To our knowledge, this is the first study to demonstrate an association between circulating HIF1α and T2D in people with severe obesity. Our data suggest that hyperglycemia may result in the accumulation of HIF1α protein, which may contribute to the development of T2D-associated complications. Hence, inhibition of HIF1α expression may exert beneficial effects on T2D and its complications.